Penerapan Peraturan Kepolisian Negara RI Nomor 6 Tahun 2019 tentang Penyidikan Tindak Pidana tentang Proses Penyidikan Terhadap Anak sebagai Pelaku Kejahatan - Lorenza, Miranda Lola; Myharto, Wiend Sakti (HUMANIORUM, 2025)
In the investigation process, an investigator can only determine someone as a suspect if there is sufficient legal and accountable evidence. Investigators must ensure that the evidence collected is strong enough to support the determination of a suspect, and that laws have been established to maintain justice and prevent errors in the legal process. Article 183 of the Criminal Procedure Code provides an explanation that a person can only be sentenced to a crime if there is a minimum of two pieces of evidence that are valid according to legal provisions. The formulation of the problem is how to implement Article 10 of Perkap No.6 of 2019 concerning the investigation of criminal acts against children as perpetrators at the Ogan Komering Ulu Selatan Police Station? And what are the obstacles faced by PPA investigators in implementing Article 10 of Perkap No.6 of 2019 concerning the investigation of criminal acts against children as perpetrators at the Ogan Komering Ulu Selatan Police Station. The research methods used are normative juridical and empirical, using secondary and primary data. The results of the research are that the implementation of Article 10 of the National Police Chief's Regulation No.6 of 2019 concerning Investigation of Criminal Offenses related to child perpetrators has been carried out through a series of very careful steps and in accordance with applicable legal provisions, while still paying attention to the best interests of the child. South Ogan Komering Ulu Police is facing several obstacles related to legal structure, legal substance and legal culture. The advice given is that PPA investigators need to make continuous efforts to increase investigators' understanding of children's rights in criminal justice, as well as the importance of a child-friendly approach at every stage of the investigation.